2008
DOI: 10.1007/s10695-008-9280-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression of three estrogen receptors in response to bisphenol A and nonylphenol in male Nile tilapias (Oreochromis niloticus)

Abstract: Environmental estrogens, such as bisphenol A (BisA) and nonylphenol (NP), have been shown to affect the estrogen receptor (ER) expression and induce male reproductive abnormalities. To elucidate molecular mechanisms of action of xenoestrogenic chemicals on the expression of estrogen receptors in the testes of Nile tilapia (Oreochromis niloticus), three full-length cDNAs respectively encoding ntERalpha, ntERbeta1 and ntERbeta2 were cloned from testes. The amino acid sequences of ntERalpha, ntERbeta1 and ntERbet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…The induction of vtg1 appears to be controlled by the estrogen receptors after binding to the ligands and the chemicals tested. In a recent report on a study of estrogen receptor cDNA cloning and gene expression in male Nile tilapias, BPA was found to induce the expression of era mRNA, but not erb1 or erb2 mRNA (Huang et al, 2010). The molecular mechanisms of vtg1 induction by TBBPA and pesticides needs to be further examined to fully understand their levels of risk and toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…The induction of vtg1 appears to be controlled by the estrogen receptors after binding to the ligands and the chemicals tested. In a recent report on a study of estrogen receptor cDNA cloning and gene expression in male Nile tilapias, BPA was found to induce the expression of era mRNA, but not erb1 or erb2 mRNA (Huang et al, 2010). The molecular mechanisms of vtg1 induction by TBBPA and pesticides needs to be further examined to fully understand their levels of risk and toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Lee et al (2013) showed that NP concentration in Taiwan river sediments was relatively higher than that in other countries (Fu et al, 2007;Lee et al, 2013;Li et al, 2004). NP is an estrogen mimic that can affect the endocrine system by disrupting signal pathways and by interacting with estrogen receptors (Huang et al, 2010;Laws et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This ER is a result of a duplication of the ER␤ gene; previously termed ER␣, ER␤, and ER␥, fish ERs were renamed ER␣, ER␤1, and ER␤2, respectively, to conform to zebrafish nomenclature [5,6]. Many tissues, of both male and female fish, co-express ER subtypes and levels can vary among tissues, genders, ontogeny, and reproductive and behavioral states [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%